Perbandingan Minat Belajar dan Hasil Belajar pada Implementasi Strategi Pembelajaran REACT (Relating, Experiencing, Applying, Cooperating, dan Transferring) dan Pendekatan Saintifik untuk Mata Pelajaran Pemrograman Berorientasi Objek di SMK Negeri 9 Medan - Syeh Umar Anggana; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
This study aims to find out the comparison of learning interests and student learning outcomes through the application of the REACT strategy and the Scientific Approach for Object Oriented Programming (PBO) subjects. This type of research is quasi-experimental, while the research design applied is non-equivalent control group design. The research subjects were students of class XI of SMK Negeri 9 Medan, while the determination of the sample was through simple random sampling technique. Data analysis used unpaired sample t-test. Collecting data using a questionnaire and questions pre-test & post-test. The questionnaire functions to measure learning interest, while the pre-test & post-test questions function to measure learning outcomes. The research was conducted by carrying out learning activities for two meetings with the control class and the experimental class. The control class uses the Scientific Approach, while the experimental class uses the REACT strategy. The results of the study indicate that the overall research instrument data has a 2-tailed significance probability value greater than 0.05 so that it is stated that there is no significant difference in learning interest and student learning outcomes. The conclusion that can be drawn is that there is no significant difference in learning interest and learning outcomes in the implementation of the REACT strategy and the Scientific Approach for Object Oriented Programming subjects at SMK Negeri 9 Medan.